Prevalence of Enteroparasites in Immunocompromised and Immunocompetent Children - G Chourio-Lozano; I Díaz; Z Rivero-Rodríguez; C Peña; E Cuenca; M Calchi; E Molero (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
Objetive: Determine the enteroparasite prevalence in immuno-compromised and Immunocompetent children in Zulia State, Venezuela. Materials and methods: Fecal samples from 78 children of both sexes, between the ages of 2 months and 12 years were distributed in 4 groups and analyzed: Undernourished (20), Oncological (20), with HIV/AIDS infection (18) and a control group (20); the copro-parasitology test, Lugol, Nair and Kinyoun stains, Ritchie concentration technique and Arakaki technique (agar in plaque) were used. Results: 29 (37,2%) children had one or several kinds of enteroparasites distributed as follows: 7/20 (35,0%) for the Undernourished and Control groups respectively, 8/20 (40,0%) for Oncology and 7/18 (38,9%) for the children with HIV/AIDS infection. The ethary group represented by the children two years of age of younger had more parasites which also occurred in undernourished control children and children from 3 to 6 years old for the Oncology group and children from 7 to 12 years old for the children with HIV/AIDS infection. The prevalent parasites were: Ascaris lumbricoides (14,3%) and Blastocystis hominis (24,5%). Conclusions: The immuno-compromised condition of these children under study (Undernourishment, Cancer and HIV/AIDS) was not significant for entero-parasite presence. Monoparasitism was prevalent in Undernourished, Oncology and Control groups and the poly-parasitism was prevalent in children with HIV/AIDS infection. The results obtained in this study represent a contribution to the knowledge of enteroparasitosis in our region.